Peran Bahasa Prancis Agrowisata bagi Stakeholder Pariwisata di Toraja sebagai upaya Peningkatan Pelayanan Bidang Pariwisata terhadap Wisatawan Eropa - Hasyim, Muhammad; Armin, Mardi Adi; latjuba, ade yolanda; kuswarini, prasuri; masdiana, masdiana; hasbullah, hasbullah (Universitas Hasanuddin, 2017)
This paper discusses alternative solutions provided in tourism development in Toraja, after the monetary crisis since 1998, which has adversely affected tourism in Toraja, which is marked by a decrease in the number of foreign tourist arrivals.Based on the results of research that has been done in 2016, drawn the conclusion is the root of the problem against the tourism business in Toraja is the lack of variation of tourist attraction, which during this time, tourism is always a mainstay is the tradition culture: Rambusolo and traditional house